Characteristics of Transformation and Low-temperature Deformation of Ti-51.1Ni Shape Memory Alloy. Issue 7 (July 2017) - Jun, Yang; Zongyue, Bi; Lei, Tian; Jingli, Wang; Haizhang, Liu
Abstract: Effects of annealing temperature on the phase transformation and the low temperature deformation characteristics in the deformed Ti-51.1Ni (at%) shape memory alloy (SMA) were investigated by differential scanning calorimetry (DSC), optical microscope (OM) and tensile test. The results show that the transformation types of Ti-51.1Ni alloy are changing from A→R/M→R→A to A→R→M/M→R→A to A→R→M/M→A (A-parent phase B2, R-R phase, M-martensite phase) upon cooling/heating along with increasing annealing temperature. The R transformation temperatures and martensite temperature hysteresis decrease, while the M transformation temperature increases and the R temperature hysteresis nearly keeps at about 6.5 °C. When deformation happen at 10 °C, the 400∼550 °C annealed Ti-51.1Ni SMA exhibits as the shape memory effect (SME) + superelasticity (SE), the 600∼700 °C annealed SMA shows SE, and the characteristics of alloy change from SME + SE to SE. In addition, the annealing recrystallization temperature of Ti-51.1Ni SMA is 590 °C, and the 590∼650 °C annealed alloy could obtain excellent capability of plastic deformation and 50.83 % values of fracture strain, so the forming processing temperature could be in the range of 590∼650 °C. When the Ti-51.1Ni alloy are used for energy consumption of damper and damping device, the suitable annealing temperature could be higher than 550 °C, and for making superelastic device, the suitable annealing temperature could be below 400 °C or above 600 °C.